Influence of rainfall on the trophic status of a brazilian semiarid reservoir - doi: 10.4025/actascibiolsci.v35i4.18261 - Francisco Ítalo Barbosa Chaves; Paulo de Freitas Lima; Renato Carrhá Leitão; Walt Disney Paulino; Sandra Tédde Santaella (Acta Scientiarum. Biological Sciences, 2013)
This study evaluated the trophic conditions of the reservoir located in the urban perimeter of the town General Sampaio, semiarid region of the Ceará State, Brazil and its relationship with seasonal variation in rainfall between 2010 and 2011. It was obtained data for Secchi disk transparency, total phosphorus, and chlorophyll a to calculate the Trophic State Index (TSI), as well as rainfall data. The Trophic State Index (TSI) proposed by Carlson (1977) and modified by Toledo Junior (1990) was used to test the influence of the seasonal variation in rainfall on hydrological variables and on trophic conditions of the reservoir in 2010 and 2011. There was seasonal variability in variables analyzed between climatic periods (rainy and dry) and trophic conditions determined through the trophic index indicated conditions ranging from oligotrophic to eutrophic during the two years analyzed in this reservoir. Under these circumstances, one may conclude that the trophic status is related to seasonal fluctuations in the hydrology of the system controlled by rainfall, which is a common feature of semiarid regions.